HUKUM PERKAWINAN KATOLIK DAN SIFATNYA. SEBUAH MANIFESTASI RELASI CINTA KRISTUS KEPADA GEREJA YANG SATU DAN TAK TERPISAHKAN - Gobai, Daniel Wejasokani; Korain, Yulianus (Jurnal Hukum Magnum Opus, 2020)
Marriage is an important idea, particularly in Christianity and generally in broader society. Generally speaking, every element of society understands marriage as the union of two persons, a man and woman, and through various processes both parties are united, binding promises before the authority to live a commitment for their whole life. For the Catholic Church, marriage is a sacrament that is a sign and means that saves and unites, in which unity between the two is prescribed in the divine plan. For some reasons, the sacrament of marriage has a variety of meanings. Among other things, besides manifesting the unity of relationship between Christ and His Church who inseparable, the Christian marriage is considered as a mean of the presence of God, who guides and accompanies, nourishes and fosters love for one another in the sacred bonds of marriage, which is inseparable and irrevocable. Perkawinan merupakan gagasan yang penting dalam kekristenan pada khususnya dan masyarakat pada umumnya. Hampir setiap elemen masyarakat, memahami perkawinan sebagai persetukuan dua pribadi, seorang pria dan wanita, dan melalui berbagai rentetan proses, keduanya bersatu, mengikat janji di hadapan otoritas yang berwenang untuk setia selamanya. Bagi Gereja katolik, perkawinan adalah sakramen yakni tanda dan sarana yang menyelamatkan dan menyatukan, yang mana persatuan di antara keduanya terlaksana  berkat penyelenggaraan ilahi. Untuk itu, sakramen Perkawinan memiliki berbagai makna, antara lain selain memanifestasikan relasi Kristus dan Gereja-Nya yang satu dan tak terpisahkan, tetapi juga berarti sarana yang menghadirkan Allah yang menuntun dan menyertai, memelihara dan memupuk cinta satu sama lain dalam ikatan suci perkawinan yang tak terbatalkan dan tak terpisahkan.